The role of deep brain stimulation in Parkinson’s disease: an overview and update on new developments - Fang JY (Dove Medical Press, 2017)
John Y Fang, Christopher Tolleson Department of Neurology, Vanderbilt University Medical Center, Nashville, TN, USA Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by the loss of neuronal dopamine production in the brain. Oral therapies primarily augment the dopaminergic pathway. As the disease progresses, more continuous delivery of therapy is commonly needed. Deep brain stimulation (DBS) has become an effective therapy option for several different neurologic and psychiatric conditions, including PD. It currently has US Food and Drug Administration approval for PD and essential tremor, as well as a humanitarian device exception for dystonia and obsessive-compulsive disorder. For PD treatment, it is currently approved specifically for those patients suffering from complications of pharmacotherapy, including motor fluctuations or dyskinesias, and a disease process of at least 4 years of duration. Studies have demonstrated superiority of DBS and medical management compared to medical management alone in selected PD patients. Optimal patient selection criteria, choice of target, and programming methods for PD and the other indications for DBS are important topics that continue to be explored and remain works in progress. In addition, new hardware options, such as different types of leads, and different software options have recently become available, increasing the potential for greater efficacy and/or reduced side effects. This review gives an overview of therapeutic management in PD, specifically highlighting DBS and some of the recent changes with surgical therapy. Keywords: Parkinson’s disease, deep brain stimulation, functional neurosurgery